Simulated in-line deployment of offshore rigid field joint - A testing concept - Reda, A.; Al-Yafei, A.; Howard, I.; Forbes, G.; McKee, Kristoffer (2016)
© 2015 Elsevier Ltd. Failure of submarine power cables have been shown to be attributed to cable field joints in 18% of cases. This high failure rate at the joining location indicates that the current acceptance testing of these joints is inadequate. The failure mode of these joints is believed to be entirely due to water ingress at the field joint location. Submarine cable field joints are required during installation due to cable repair, joining of insufficient manufactured cable lengths or when the lay process has to be abandoned due to the sea state. Current design guidance for cable field joints suggests sea trails to determine if the proposed field joining technique is acceptable. Sea trails, however, are often prohibitively expensive, such that a set of standardised onshore testing regimes which improves both the reliability and affordability of these tests would be advantageous. This paper outlines a recent cable field joint onshore testing regime to ensure the cable joint integrity during the laying process as well as serviceability in operational life. The paper outlines a process for simulation of the calculated cable laying tension and bend radius with a set of physical tests developed for mechanical and water ingress protection.